NEEDS ASSESMENT TENTANG PROMOSI KESEHATAN REPRODUKSI PADA MAHASISWA FAKULTAS KEDOKTERAN DAN ILMU-ILMU KESEHATAN UNSOED - Elviera Gamelia; Colti Sistiarani (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2011)
ABSTRACT Pursuant to result health of reproduction survey shown at this group have low knowledge to health of reproduction. There are tendency of behavior of free seks in General region of Soedirman Univercity the including student of FKIK. Target of this research was conducted health of reproduction promotion need assessment for student of FKIK Unsoed. Research type taken was research qualitative; with device of rapid procedures assessment (RAP). Type Sampling which used in this research wass sampling case critical and of homogeneous sampling of subjek especial in this research is student of FKIK Unsoed . Amount of especial informen is 10 people. Data analysis qualitative the used is analysis content. This Research result was knowledge of university student concerning health of reproduction have good. The risk behavioral of university student health reproduction divided become three behavior is ; risk behavior, behavioral of prevention of health problem, behavioral thridhandling of problem health of reproduction. University student require promotion reproduction health at university student.. Promotion model reproduction health of long-range which required and most precise for university student and as according to opinion of faculty leader, majors leader and hygienist reproduce is consultancy health of reproduction. Student shall lessen behavior of risk, faculty leader execute commitment to conducted promotion health of reproduction for university student required facilities and basic facilities facility and policy. Key words : need assessment , health of reproduction Kesmasindo Volume 4, Nomor 2, Juli 2011, hlm. 159-174